Kajian Kualitas Produk Susu Pasteurisasi Hasil Penerapan Rantai Pendingin - Wulandari, Z.; Taufik, E.; Syarif, M. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
The production chain of fresh milk pasteurized milk with different quality of cold chain has an influence on physicochemical and microbiological quality. The objective of this study is to assessment the quality of pasteurized milk products as results of applying the cold chain. The research was conducted on pasteurized milk production chain from farm to consumer consisting of dairy farms of Cibungbulang Livestock Business Area (KUNAK), milk processing unit of SUA Fapet, and street food outlet. Analysis of the quality of fresh milk and pasteurized milk include physicochemical analyzes such as pH, density, fat, protein, dry matter, and nonfat dry matter as well as microbiological quality analyzes such as Total Plate Count, Escherichia coli, and Staphylococcus aureus. It can be concluded that physicochemical qualities include pH, specific gravity, fat, protein, dry matter, and nonfat dry matter and microbiological quality including Total Plate Count, Escheriachia coli and Staphylococcus aureus influenced by production chains with different cold chain quality (P <0.05) .